Recent Development in Ammonia Stripping Process for Industrial Wastewater Treatment - Kinidi, Lennevey; Wei, Ivy Tan Ai; Noraziah, binti Abdul Wahab; Khairul Fikri, bin Tamrin; Hipolito, Cirilo Nolasco; Shanti Faridah, binti Salleh (Hindawi Publishing, 2018)
It is noteworthy to highlight that ammonia nitrogen contamination in wastewater has been reported to pose a great threat to the environment. This conventional method of remediating ammonia nitrogen contamination in wastewater applies the packed bed tower technology. Nevertheless, this technology appears to pose several application issues. Over the years, researchers have tested various types of ammonia stripping process to overcome the shortcomings of the conventional ammonia stripping technology. Along this line, the present study highlights the recent development of ammonia stripping process for industrial wastewater treatment. In addition, this study reviews ammonia stripping application for varied types of industrial wastewater and several significant operating parameters. Furthermore, this paper discusses some issues related to the conventional ammonia stripper for industrial treatment application. Finally, this study explicates the future prospects of the ammonia stripping method. This review, hence, contributes by enhancing the ammonia stripping treatment efficiency and its application for industrial wastewater treatment.